Thick junction broadband organic photodiodes - Paul Meredith (Laser & Photonics Reviews, 2014)
Inorganic semiconductor-based broadband photodetectorsare ubiquitous in imaging technologies such as digitalcameras and photometers. Herein a broadband organic photodiode(OPD) that has performance metrics comparable orsuperior to inorganic photodiodes over the same spectral rangeis reported. The photodiode with an active layer comprisedof a poly[N-9-heptadecanyl-2,7-carbazole-alt-5,5-(4,7-di-2-thienyl-2,1,3-benzothiadiazole)]:[6,6]-phenyl-C71-butyric acidmethyl ester bulk heterojunction blend had a dark current < 1nA/cm2, specific detectivity of ∼ 1013 Jones, reverse bias −3 dBfrequency response of 100 kHz to 1 MHz, and state-of-the-artLinear Dynamic Range for organic photodiodes of nine ordersof magnitude (180 dB). The key to these performance metricswas the use of a thick junction (700 nm), which flattened thespectral response, reduced the dark current and decreasedperformance variations. The strategy also provides a route tolarge area defect free “monolithic” structures for low noiseintegrated photo-sensing, position determination, or contact,non-focal imaging.